Peningkatan Kemampuan Membaca Al-Qur’an Melalui Program Klinik Al Qur’an di SMK Negeri 15 Jakarta - Arti Yulyani; Shobah Shofariyani Iryanti (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The life of every Muslim cannot be separated from the Qur'an, because it is a guide and guide to life. However, in reality, many of the current generation still do not understand the basics of reading the Qur'an. The purpose of this research is to determine the efforts of PAI teachers to improve the ability to read the Al Qur'an of students at SMK Negeri 15 Jakarta. The subjects of this research were PAI teachers at SMK Negeri 15 Jakarta. The object of this research is the program